The effects of chronic administration of stimulant and non-stimulant medications on executive functions in ADHD: A systematic review and meta-analysis - Isfandnia, Ferdous; El Masri, Sahid; Radua, Joaquim; Rubia, Katya (Neuroscience and biobehavioral reviews, 2024)
Attention-Deficit/Hyperactivity Disorder (ADHD) is associated with executive function deficits that are improved with medications. However, meta-analyses of stimulant effects on cognition have mostly tested single-dose effects, and there is no meta-analysis of non-stimulant effects. This systematic review and meta-analysis tested the clinically more relevant longer-term effects of Methylphenidate (20 studies; minimum 1 week) and Atomoxetine (8 studies; minimum 3 weeks) on reaction time, attention, inhibition, and working memory, searching papers on PubMed, Embase, Ovid MEDLINE, and PsycINFO. The meta-analysis of 18 studies in 1667 subjects showed that methylphenidate was superior to placebo in all cognitive domains with small to medium effect sizes (Hedges g of 0.34–0.59). The meta-analysis of atomoxetine included 7 studies in 829 subjects and showed no effects in working memory, but superior effects in the other domains with medium to large effect sizes (Hedge’s g of 0.36–0.64). Meta-regression analysis showed no drug differences on cognitive effects. The meta-analyses show for the first time that chronic Methylphenidate and Atomoxetine have comparable effects of improving executive functions in people with ADHD. •First meta-analysis of chronic medication effects on cognition in ADHD.•Cognitive domains included attention, inhibition, reaction time and working memory.•Chronic methylphenidate improved performance on all cognitive domains.•Chronic Atomoxetine improved performance on all domains except working memory.•Methylphenidate and Atomoxetine had comparable effects on improving cognition in ADHD.